Suppression of inflammation-induced lung cancer cells proliferation and metastasis by exiguaflavanone A and exiguaflavanone B from Sophora exigua root extract through NLRP3 inflammasome pathway inhibition - Arjsri, Punnida; Srisawad, Kamonwan; Semmarath, Warathit; Umsumarng, Sonthaya; Rueankham, Lapamas; Saiai, Aroonchai; Rungrojsakul, Methee; Katekunlaphan, Trinnakorn; Anuchapreeda, Songyot; Dejkriengkraikul, Pornngarm (Frontiers in Pharmacology, 2023)
Objective: Non-small cell lung cancer (NSCLC) is recognized for its aggressive nature and propensity for high rates of metastasis. The NLRP3 inflammasome pathway plays a vital role in the progression of NSCLC. This study aimed to investigate the effects of S. exigua extract and its active compounds on NLRP3 regulation in NSCLC using an in vitro model. Methods:S. exigua was extracted using hexane, ethyl acetate and ethanol to obtain S. exigua hexane fraction (SE-Hex), S. exigua ethyl acetate fraction (SE-EA), and S. exigua ethanol fraction (SE-EtOH) respectively. The active compounds were identified using column chromatography and NMR analysis. A549 cells were primed with lipopolysaccharide (LPS) and adenosine triphosphate (ATP) for activated NLRP3 inflammasome. The anti-inflammatory properties were determined using ELISA assay. The anti-proliferation and anti-metastasis properties against LPS-ATP-induced A549 cells were determined by colony formation, cell cycle, wound healing, and trans-well migration and invasion assays. The inflammatory gene expressions and molecular mechanism were determined using RT-qPCR and Western blot analysis, respectively. Results: SE-EA exhibited the greatest anti-inflammation properties compared with other two fractions as evidenced by the significant inhibition of IL-1β, IL-18, and IL-6, cytokine productions from LPS-ATP-induced A549 cells in a dose-dependent manner (p < 0.05). The analysis of active compounds revealed exiguaflavanone A (EGF-A) and exiguaflavanone B (EGF-B) as the major compounds present in SE-EA. Then, SE-EA and its major compound were investigated for the anti-proliferation and anti-metastasis properties. It was found that SE-EA, EGF-A, and EGF-B could inhibit the proliferation of LPS-ATP-induced A549 cells through cell cycle arrest induction at the G0/G1 phase and reducing the expression of cell cycle regulator proteins. Furthermore, SE-EA and its major compounds dose-dependently suppressed migration and invasion of LPS-ATP-induced A549 cells. At the molecular level, SE-EA, EGF-A, and EGF-B significantly downregulated the mRNA expression of IL-1β, IL-18, IL-6, and NLRP3 in LPS-ATP-induced A549 cells. Regarding the mechanistic study, SE-EA, EGF-A, and EGF-B inhibited NLRP3 inflammasome activation through suppressing NLRP3, ASC, pro-caspase-1(p50 form), and cleaved-caspase-1(p20 form) expressions. Conclusion: Targeting NLRP3 inflammasome pathway holds promise as a therapeutic approach to counteract pro-tumorigenic inflammation and develop novel treatments for NSCLC.